2010
DOI: 10.1007/s10646-010-0580-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of comet assay in the study of DNA damage and recovery in rohu (Labeo rohita) fingerlings after an exposure to phorate, an organophosphate pesticide

Abstract: Labeo rohita (rohu) fingerlings were exposed to different concentrations (0.001, 0.002 and 0.01 ppm) of phorate, an organophosphate pesticide; samplings were done at 24, 48, 72 and 96 h. The study was carried out to evaluate tissue specific genotoxic effects produced by phorate, on three different tissue systems and to assess DNA repair response in fish. Results of tissue specific DNA damage experiments showed low baseline damage in blood cells followed by gill and liver cells in control individuals whereas mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 35 publications
(43 reference statements)
4
26
0
Order By: Relevance
“…In this paper, the authors observed an increase in DNA damage in the erythrocytes of these fish [26]. The same results were observed in studies with the phorate pesticide, a genotoxic organophosphate, in fingerlings of Labeo rohita (Cyprinidae) [27], and Roundup ® herbicide, evaluated in Anguilla anguilla (Anguillidae), also displayed genotoxicity [28]. The results obtained in this study corroborate previous studies with other pesticides and support the claim that the comet assay is a highly sensitive method for the detection of DNA damage induced by environmental pollutants.…”
Section: Discussionsupporting
confidence: 83%
“…In this paper, the authors observed an increase in DNA damage in the erythrocytes of these fish [26]. The same results were observed in studies with the phorate pesticide, a genotoxic organophosphate, in fingerlings of Labeo rohita (Cyprinidae) [27], and Roundup ® herbicide, evaluated in Anguilla anguilla (Anguillidae), also displayed genotoxicity [28]. The results obtained in this study corroborate previous studies with other pesticides and support the claim that the comet assay is a highly sensitive method for the detection of DNA damage induced by environmental pollutants.…”
Section: Discussionsupporting
confidence: 83%
“…Phorate, an organophosphate pesticide, is genotoxic to Labeo rohita. Specimens contaminated by this pesticide when maintained in water free of pollution also showed the ability to repair DNA damage (MOHANTY et al, 2011). Using the comet assay, Groff et al (2010) detected a reduction in DNA damage to the erythrocytes of Neotropical fish (Arapaima gigas and Colossoma macroporum) 12 hours after exposure to UVR-B (ultraviolet radiation B) and suggest that nucleotide excision repair is involved in DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Many reviews details the employment of comet assay in the assessment of the genotoxic potential of many compounds, which notably include metals, pesticides, opiates, nitrosamines and anticancer drugs (Collins, 2004). A significant advantage of the comet assay is its applicability to any eukaryotic organism and nucleated cell type (Mohanty et al, 2009a(Mohanty et al, , 2009b(Mohanty et al, , 2011. This assay can be applied both in vitro and in vivo conditions after an exposure to different potent genotoxic and mutagenic agents (.…”
Section: Comet Assaysmentioning
confidence: 99%
“…A study was carried out by Mohanty et al, (2009aMohanty et al, ( , 2009bMohanty et al, ( and 2011 with an objective to study the genotoxic effects of two pesticides, phorate, an organophosphate and furadan, a carbamate on rohu (Labeo rohita) fingerlings. To evaluate the DNA damage, rohu fingerlings were exposed to control, 0.001, 0.002 and 0.01ppm of phorate control, 0.002, 0.004 and 0.02ppm of furadan for a total time period of 96h.…”
Section: Comet Assaymentioning
confidence: 99%